Sustainable Marine Macroalgal Polysaccharide Films and Coatings: Toward Active and Intelligent Food Packaging System - Sinha, Sweta (Diponegoro University, 2025)
Marine macroalgal polysaccharides have emerged as sustainable biopolymers with immense potential for developing active and intelligent food packaging systems. Derived from abundant and renewable seaweed biomass, polysaccharides such as alginate, agar, carrageenan, laminarin, ulvan and fucoidan exhibit excellent film-forming ability, biodegradability, and non-toxicity. Their intrinsic antioxidant and antimicrobial properties make them ideal for packaging materials that not only protect food but also enhance shelf life and quality. This review (2020-2025) comprehensively examines the extraction techniques, structural diversity and functionalities of marine polysaccharide, highlighting their suitability for edible films, coatings, and biodegradable bioplastics. Recent advancements in polymer blending, nanocomposite formation, and cross-linking strategies are discussed, which significantly improve mechanical strength, thermal stability, and barrier properties. Additionally, the integration of natural bioactive compounds enables real-time monitoring of food freshness, transforming conventional packaging into active and intelligent systems. Although challenges such as moisture sensitivity, moderate mechanical strength, and production scalability remain, marine macroalgal polysaccharides represent a promising and sustainable alternative to conventional plastics. By supporting circular economy principles and sustainable packaging initiatives, these biopolymers present innovative solutions to mitigate plastic pollution, reduce food waste, and promote environmental responsibility. This review highlights their potential to catalyze a paradigm shift in the food packaging sector, advancing high-performance, safe, and eco-friendly applications.